2014
DOI: 10.1002/bmc.3151
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative determination of euphol in rat plasma by LC‐MS/MS and its application to a pharmacokinetic study

Abstract: Euphol is a potential pharmacologically active ingredient isolated from Euphorbia kansui. A simple, rapid, and sensitive method to determine euphol in rat plasma was developed based on liquid chromatography-tandem mass spectrometry (LC-MS/MS) for the first time. The analyte and internal standard (IS), oleanic acid, were extracted from plasma with methanol and chromatographied on a C18 short column eluted with a mobile phase of methanol–water–formic acid (95:5:0.1, v/v/v). Detection was performed by positive io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The RE determined from all of the stability tests were within ±6.92% of each other (Table III). The results demonstrated that the accuracy, precision, recovery and stability tests met the criteria for quantitative determination in biological samples (28).…”
Section: Resultsmentioning
confidence: 85%
“…The RE determined from all of the stability tests were within ±6.92% of each other (Table III). The results demonstrated that the accuracy, precision, recovery and stability tests met the criteria for quantitative determination in biological samples (28).…”
Section: Resultsmentioning
confidence: 85%
“…Regarding the latest cited Euphorbia tirucalli, it is a common plant found in Brazil and by far the most studied species from the Euphorbia family in concern to its major compound: euphol. Studies on euphol chemical structure using x-ray crystallographic, Fourier transform-ion cyclotron resonance mass spectrometry, tandem mass spectrometry, and gas chromatography coupled mass spectrometry, as well as its quantitative determination in the rat plasma by liquid chromatography-tandem mass spectrometry allowed a better understanding of this compound chemical and biological behavior [222][223][224]. Importantly, ethnopharmacology evidences have lead and contributed to studies on the anticancer and anti-inflammatory effects of this triterpene compound, as by many years the plants from this family have been used as folk phytomedicine to treat tumors and inflammation states [221].…”
Section: Eupholmentioning
confidence: 99%